2020
DOI: 10.1111/obr.13016
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of socioeconomic inequalities in dietary behaviours among youth: A systematic review

Abstract: Children and adolescents with a lower socioeconomic position have poorer dietary behaviours compared to their counterparts with a higher socioeconomic position. A better understanding of the mechanisms behind such socioeconomic inequalities is vital to identify targets for interventions aimed at tackling these inequalities. This systematic review aimed to summarize existing evidence regarding the mediators of socioeconomic differences in dietary behaviours among youth. A systematic literature search of MEDLINE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 67 publications
(132 reference statements)
2
15
0
6
Order By: Relevance
“…For students to achieve the competences described in the FH curriculum, it requires they possess in-depth knowledge of food and nutrition. The importance of nutrition and food knowledge is also supported by literature regarding adolescent food literacy and dietary behaviour (Amin et al, 2019;Mekonnen et al, 2020;Ronto et al, 2016). Therefore, nutrition education should get a higher priority in FH classes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For students to achieve the competences described in the FH curriculum, it requires they possess in-depth knowledge of food and nutrition. The importance of nutrition and food knowledge is also supported by literature regarding adolescent food literacy and dietary behaviour (Amin et al, 2019;Mekonnen et al, 2020;Ronto et al, 2016). Therefore, nutrition education should get a higher priority in FH classes.…”
Section: Discussionmentioning
confidence: 91%
“…They found knowledge of food systems, cooking, and nutrition, cooking skills and self-efficacy regarding eating to be important food literacy domains. A recent systematic review found self-efficacy and knowledge to modify socioeconomic differences in dietary behaviour among youths (Mekonnen et al, 2020). Also, according to an Australian study (Ronto, Ball, Pendergast, & Harris, 2016), adolescents ranked food and nutrition knowledge to be the most important aspect impacting their dietary behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Our intervention groups were comparable in their socio-economic and educational levels (data not shown). However, we do not preclude any potential favourable influence of privileged socio-economic and educational status on the baseline and changes in our participants' pulse-consumption behaviours, as these factors are known to affect dietary behaviours [59,60]. Therefore, our observations may be skewed toward women with a higher degree of self-awareness about their health at baseline and need to be replicated across cohorts with different socio-demographic backgrounds.…”
Section: Discussionmentioning
confidence: 92%
“…Instead, students with a disadvantaged position may benefit more from a healthy food environment at school [ 43 ]. Improving nutritional knowledge (school and family), establishing routines or rules related to meals, promoting home food availability of fruits and less healthful alternatives can be valuable ways of promoting healthy eating and reducing inequalities in dietary behaviors in adolescents [ 44 ]. Greater economic and educational resources can contribute to healthier dietary behavior through increased food budgets, nutritional knowledge, planning food purchases, and cooking skills [ 45 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%